Probiotics Ingestion Does Not Directly Affect Thyroid Hormonal Parameters in Hypothyroid Patients on Levothyroxine Treatment - Spaggiari, Giorgia; Brigante, Giulia; De Vincentis, Sara; Cattini, Umberto; Roli, Laura; De Santis, Maria Cristina; Baraldi, Enrica; Tagliavini, Simonetta; Varani, Manuela; Trenti, Tommaso; Rochira, Vincenzo; Simoni, Manuela; et al. (Frontiers in Endocrinology, 2017)
Purpose: The relationship between probiotics and levothyroxine (LT4) requirement has not yet been investigated. The aim of this study was to assess whether a mixture of highly charged Lactobacilli and Bifidobacteria (VSL#3®) is able to influence LT4 metabolism acting on the gut microbiota. Methods: A prospective, randomized, single-blind, controlled, investigator-started clinical trial was carried out. Patients with primary hypothyroidism were randomly assigned to the study (VSL#3®+ LT4) and the control group (LT4). A two-months treatment phase was followed by two months of follow-up. Clinical examination, blood tests for thyroid function and for peripheral tissue markers of thyroid hormones (PTM) were performed monthly. LT4 dose adjustments were performed when necessary. Results: Thirty-nine patients were enrolled in the study group and 41 in the control group. No difference in thyroid function (thyroid-stimulating hormone (TSH), free triiodothyronine (fT3) and free thyroxine (fT4)) and PTM was found between groups and among visits. FT3/fT4 ratio was directly correlated to TSH at each visit in both groups, with the exception of the first evaluation of probiotics-treated subjects (rho=0.287, p=0.076). LT4 daily dose adjustments occurred more frequently in the control than in the study group (p=0.007), despite no differences in the mean LT4 daily dose. In particular, LT4 doses were increased 6 times in the control group and decreased 4 times in the study group. Conclusions: VSL#3® does not directly alter thyroid functional compensation. A probiotics-mediated influence on thyroid hormones homeostasis is suggested since probiotics supplementation could be able to prevent serum hormonal fluctuations.